Pengaruh Fraud Hexagon Model Terhadap Fraudulent Laporan Keuangan pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2016-2019 - Samuel Gevanry Sagala; Valentine Siagian (Universitas Kristen Maranatha, 2021)
Abstract This study aims to determine the effect of the fraud hexagon model, namely pressure (stimulus) which is proxied by financial targets and financial stability, capabilities that are proxied by changes in directors, opportunities proxied by ineffective monitoring, rationalization proxied by change in auditors, arrogance proxied by frequent number of CEO's picture, and collusion proxied by government projects, political connections and state-owned enterprises to fraudulent financial statements. The sample of this study is the food and beverage sub sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2019. This study uses secondary data, namely financial reports and annual reports. Based on the purposive sampling method, the number of companies sampled in this study was 18 companies from a total of 32 companies registered and analyzed by multiple linear regression analysis using the SPSS 25 program. The results of this study found that the elements of pressure that are proxied by financial targets and financial stability had a significant effect on fraudulent financial statements. Meanwhile, change of directors, ineffective monitoring, change in auditors, frequent number of CEO's pictures, government projects, political connections and state-owned enterprises have no significant effect on fraudulent financial statements in food and beverage sub sector manufacturing companies listed on the IDX in 2016- 2019. Keywords: Fraudulent Financial Statement, and Fraud Hexagon Model